Sexual Selection Significance of Littoraria scabra (Gastropoda: Littorinidae) in Tombariri Mangrove - Lalita, Jans Dj. (JURNAL PERIKANAN DAN KELAUTAN TROPIS, 2023)
Evidence for sexual selection was found in Littoraria scabra in gastropods as low-level animals with various fact big female preference strong to follow the mucosal track of big females, male-male competition for copulating big female, fire frequency of being the big female shell and big male mating longer time on the big female. Keywords: Littoraria scabra, sexual selection, mucosal track, mating, mangrove Abstrak Temuan penelitian signifikansi seleksi seksual L.scabra beroperasi dalam gastropoda sebagai hewan tingkat rendah adalah terbukti dengan berbagai fakta preferensi kuat jantan yang besar ikut jejak betina besar, kompetisi antar jantan bagi kopulasi dengan betina besar, frekuensi lebih banyak jantan besar menaiki cangkang betina besar dan jantan besar kopulasi lebih lama pada betina besar. Kata Kunci. - Littoraria scabra, seleksi seks, jejak mukosa, kawin dan mangrove